HARMONI DI BANJARAN: INTERAKSI SUNNI-SYIAH - Efa Ida Amaliyah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This paper shows the interaction of Sunni- Shia followers in Banjaran Bangsri, Jepara and the violence impact experienced by Shia followers in many regions toward Shia followers in Banjaran Bangsri.The relationship between Sunni and Shia shows a harmonious life in social interaction. They realize that they have different ways of worship but they do not want to widen those differences. They live together in socio-humanitarian relation. They respect each other. It occurs because the existence of Mbah Muhammad Arif who unified Sunni and Syiah. Mbah Muhammad Arif was the founder of Banjaran as well as the Islam disseminator at Banjaran. There is no conflict between Sunni-Shia followers although there was any religious sentiment after Sunni-Syiah conflict in Sampang Madura and it does not influence the relationship between Sunni-Syiah at Banjaran Bangsri Jepara.